Large floods, alluvial overprint, and bedrock erosion. Issue 9 (18th October 2012) - Turowski, Jens M.; Badoux, Alexandre; Leuzinger, James; Hegglin, Ramon
ABSTRACT Depending on their behaviour during extreme floods, streams can be divided into two distinct classes, which derive from a simple threshold model of transport dynamics. 'Flood‐cleaning' streams erode during high flows and deposit during small and medium flows. 'Flood‐depositing' streams deposit during high flows and erode during small and medium flows. Using published descriptions of the geomorphic effects of large floods, rivers with a wide range of drainage areas and other characteristics are classified as either 'flood‐cleaning' or 'flood‐depositing'. In bedrock channels, this behaviour can lead to a feedback effect, the 'overprint effect', between sediment transport processes and bedrock erosion, which can modulate long‐term bedrock erosion rates. The 'overprint effect' arises when alluvium covers the bedrock and typical alluvial channel forms (e.g. meandering or braiding patterns, armour layers or bedforms) develop, which influence sediment transport rates. This effect may accelerate or decelerate sediment export from a reach, causing increased or decreased long‐term bedrock erosion rates. The 'overprint effect' is illustrated using field data from the Erlenbach, Switzerland, and its implications for channel dynamics and bedrock erosion are discussed. Copyright © 2012 John Wiley & Sons, Ltd.